2001
DOI: 10.1002/app.1377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shearing on crystallization behavior of poly(ethylene terephthalate)

Abstract: ABSTRACT:The shear-induced crystallization behavior of PET was investigated by measuring the time-dependent storage modulus (GЈ) and dynamic viscosity (Ј) with a parallel-plate rheometer at different temperatures and shear rate. The morphology of shear-induced crystallized PET was measured by DSC, X-ray, and polarizing optical microscopy. When a constant shear rate was added to the molten polymer, the shear stress increased with the time as a result of the orientation of molecular chains. The induction time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
4
10
0
Order By: Relevance
“…However, at the lower temperatures of 150 and 152°C, a rapid increase of the storage modulus occurs as a function of time as a result of shear-induced crystallization of the polymer melt. Similar results have been observed by others on poly (εlactone),39 polyethylene,24,34 and poly(ethylene terephthalate)40 melts.The work of de Gennes in dilute solutions of polymers has revealed that during flow the polymer chains undergo a step change from a random coil to a fully extended chain conformation at a critical strain rate, without any intermediate stable chain conformations 41. The subsequent studies of Keller et al13 have provided experimental evidence of the coil-stretch transition in polymer crystallization under shear and extension, demonstrating that as the strain rate is increased during deformation there is an abrupt change in birefringence indicative of the formation of a fullyextended chain conformation at the critical strain rate.…”
supporting
confidence: 91%
“…However, at the lower temperatures of 150 and 152°C, a rapid increase of the storage modulus occurs as a function of time as a result of shear-induced crystallization of the polymer melt. Similar results have been observed by others on poly (εlactone),39 polyethylene,24,34 and poly(ethylene terephthalate)40 melts.The work of de Gennes in dilute solutions of polymers has revealed that during flow the polymer chains undergo a step change from a random coil to a fully extended chain conformation at a critical strain rate, without any intermediate stable chain conformations 41. The subsequent studies of Keller et al13 have provided experimental evidence of the coil-stretch transition in polymer crystallization under shear and extension, demonstrating that as the strain rate is increased during deformation there is an abrupt change in birefringence indicative of the formation of a fullyextended chain conformation at the critical strain rate.…”
supporting
confidence: 91%
“…However, as reported by Bonnet et al8 for a DGEBA/MCDEA system with a low PEI concentration showing a particulate structure, RIPS from an epoxy matrix was followed by a rapid decrease of η* instead of the increase that takes place for sPS–(DGEBA/MCDEA) mixtures. Additionally, it is well known that during the isothermal crystallization of semicrystalline thermoplastics, η* increases when crystallization starts,24–27 and this confirms CIPS in the sPS–(DGEBA/MCDEA) system.…”
Section: Resultssupporting
confidence: 56%
“…Few works [47,48] are devoted to the engineering polymers which are as important as the commodity plastics in practical applications. It is maybe because of the difficulty in handling the in situ experiments of most engineering polymers such as poly(ethylene terephthalate) (PET) and poly(phenylene sulfide) (PPS) due to their high melting temperatures and the associated possibility of degradation.…”
Section: Introductionmentioning
confidence: 99%